(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tarasenko R. O., Harina S. M. Stages of creation of module of the automated system of support of scientific researches at preparation of ecologists. The necessity of development and application modules of automated support systems research in the preparation of environmentalists. An option of the module of the system to determine water quality. Noted features of this module using the software package MathCAD.